Geomatic analysis of land use change in the Copalita River sub-basin, Oaxaca - Sandoval-García, Celestino; Cantú-Silva, Israel (Ecosistemas y Recursos Agropecuarios, 2022)
The present study aims to evaluate the change in vegetation cover and land use of the Copalita River sub-basin, Oaxaca, for the period 1995- 2015. To determine the land use change, orthophotos were used for the 1995 period and high-resolution satellite images for 2015, which were processed and analyzed in the QGIS 2.18.25 program. The results indicate that medium deciduous forest presented a change rate of -0.84%, savannah -0.66%, pine-oak forest -0.65%, medium sub-evergreen forest -0.52%, mountain mesophilic forest -0.27%, medium subdeciduous forest - 0.23%, oak-pine forest -0.23%, gallery forest -0.17% and oyamel forest with -0.05%. Pine forest presented a gain of 0.35%, agriculture 0.66% and pasture 1.12%. These changes occur throughout the sub-basin, however, in the upper part, mainly a recovery of forest cover was observed, since agricultural production systems and pastures were converted into plantations and reforestations. Therefore, it is important to continue promoting different practices that allow the conservation and recovery of degraded areas of the sub-basin, such as pine plantations, agrosilvicultural systems, management of fragmented forest and paying for the hydrological services.